Bisphenol A alters transcript levels of biomarker genes for major depressive disorder - Ribeiro-Varandas, Edna (2015)
Major depressive disorder is a moderately heritable disorder characterized by one or more major depressive episodes. Laboratory tests to suport MDD diagnosis are not available. Diagnosis and treatment are based on various signs and symptoms not always fitting into strict diagnostic categories. Research for biological markers of neuropsychiatric disorders has been a challenge.